EXERCISE STRESS TESTING FOR EVALUATING SYNCOPE IN ATHLETES: A NARRATIVE REVIEW - Patryk Macuk; Anna Leśniewska; Julia Tarnowska; Filip Szydzik; Bartosz Żegleń; Michał Gniedziejko; Jakub Roszak; Oliwia Sójkowska-Sławińska; Aleksandra Gradek (International Journal of Innovative Technologies in Social Science, 2025)
Objectives: Syncope in athletes presents a complex diagnostic challenge requiring systematic evaluation to differentiate benign neurally-mediated causes from potentially life-threatening cardiac conditions. Unrecognized cardiovascular disease in athletes can lead to sudden cardiac death, making accurate risk stratification essential for athlete safety and appropriate return-to-play decisions. We aim to provide a comprehensive synthesis of current evidence regarding the indications, protocols, diagnostic yield, and limitations of exercise stress testing in athletes presenting with syncope. Methods: We conducted a narrative literature review of PubMed databases from 2004-2025, focusing on studies involving athletic populations and recent consensus statements from major cardiovascular and sports medicine organizations. Evidence was synthesized from observational studies, clinical guidelines, and expert consensus documents. Key findings: Exercise stress testing is strongly recommended for all athletes with exertional syncope, with sport-specific, maximal-effort protocols yielding arrhythmic or ischemic findings in 15-25% of cases. Negative predictive values approach 95% when proper protocols are employed, significantly reducing the probability of exercise-induced life-threatening events, though residual risk remains. Current evidence supports individualized testing protocols rather than generic clinical protocols designed for ischemia detection. Integration with comprehensive clinical assessment, ECG, echocardiography, and risk factor evaluation optimizes diagnostic accuracy and clinical decision-making. Conclusions: Sport-specific, effortful exercise stress testing serves as a pivotal diagnostic tool and safety gatekeeper in athletic syncope evaluation. When integrated within systematic algorithms it enables accurate risk stratification, specialist referral, and evidence-based return-to-play decisions. Future research should focus on protocol validation, long-term outcome studies, and integration of emerging technologies for further enhancement of diagnostic precision.